Giro de folia: o caminhar das gerações uma instalação em artes visuais - Sousa, Karina Alves de (2018)
Giro de Folia: the walk of the generations is a research that had as objective the construction of an installation in the scope of the Visual Arts. For its accomplishment, I used of two languages, the Photographs and the Objects. My intention with Photography was to make artistic records of the Folia de Reis, narrate stories through images, show the intricacies of the ritual and my experiences within the tradition. On the other hand the objects can be understood as symbols of these events, "things" that have gained affective meaning in the course of my life as a foliã. The installation, it self, is the allusion to a house of Folia, through the sensitization of a space and also a tribute to the memory of my grandfather. The thematic motivation of the work is the Folia de Reis, more specifically Folia Irmãos Tavares II, which I study with the intention of making this family heritage transmitted by my grandfather for another generation. Through its iconography, I come to understand and re-signify this popular culture, relying on the memories derived from my experiences in the Giros de Folia.